2012
DOI: 10.1111/j.1600-0536.2012.02083.x
|View full text |Cite
|
Sign up to set email alerts
|

Allergic contact dermatitis induces upregulation of identical microRNAs in humans and mice

Abstract: These are the first results indicating that microRNAs may be involved in the pathogenesis of allergic contact dermatitis, and they show that mouse models are valuable tools for further study of the involvement of microRNAs in allergic contact dermatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(67 citation statements)
references
References 20 publications
4
62
0
1
Order By: Relevance
“…These authors later reported increased T H 1 polarization in mice lacking miR-21 (Lu et al, 2011). Increases in expression of miR-21 in both human and mouse skin samples following sensitization and challenge with the chemical sensitizer diphenylcyclopropenone has also been identified (Vennegaard et al, 2012). Using peripheral blood samples of patients with allergic asthma, research investigating the role of miR-155 in allergic disease suggests that over-expression promotes CD4 þ T-cells to differentiate to T H 1 cells while lower expression promotes a T H 2 response (Zhang et al, 2012).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…These authors later reported increased T H 1 polarization in mice lacking miR-21 (Lu et al, 2011). Increases in expression of miR-21 in both human and mouse skin samples following sensitization and challenge with the chemical sensitizer diphenylcyclopropenone has also been identified (Vennegaard et al, 2012). Using peripheral blood samples of patients with allergic asthma, research investigating the role of miR-155 in allergic disease suggests that over-expression promotes CD4 þ T-cells to differentiate to T H 1 cells while lower expression promotes a T H 2 response (Zhang et al, 2012).…”
Section: Discussionmentioning
confidence: 94%
“…The central importance of miRNA regulation in cellular function is becoming clearer as more miRNA targets are discovered. While information regarding roles of miRNA in chemical sensitization are limited, recent research suggests involvement of miRNA in both chemical-induced contact hypersensitivity and asthma (Lu & Rothenberg, 2013;Vennegaard et al, 2012;Zhang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…MiR-21 suppresses TLR2 signaling, and IL-13 can upregulate miR-21 expression in human airway epithelial cells [53]. The upregulation of miR-21, miR-142-3p, miR-142-5p, and miR-223 was observed both in human and mouse allergic contact dermatitis [54]. Esophageal miRNA expression profile was investigated by microarray from human esophageal tissues of eosinophilic esophagitis (EoE) patients and controls, where the most upregulated miRNAs were miR-21 and miR-223, and the most downregulated one was miR-375.…”
Section: Further Myeloid Mirnas With Well Characterized Effectsmentioning
confidence: 99%
“…87 Notably, miRNAs upregulated in other allergic disorders, including miR-21, miR-146, and miR-223, are also upregulated in the skin of patients with atopic dermatitis. 42,88 In addition, Sonkoly et al found that miR-155 was one of the highest upregulated miRNAs in skin biopsies from patients with atopic dermatitis compared to healthy controls. 79 Topical exposure of non-lesional skin of atopic dermatitis patients with relevant allergens could induce miR-155 expression.…”
Section: Atopic Dermatitismentioning
confidence: 99%